EU presidencies between politics and administration : the governmentality of the Polish, Danish and Cypriot trio presidency in 2011-2012 /: the governmentality of the Polish, Danish and Cypriot trio presidency in 2011-2012. (2016) - Jensen, Mads Dagnis; Nedergaard, Peter
No abstract available